3D flower-like ironphthalocyanine hierarchical microstructures: solvothermal-fabrication and high visible light photocatalytic properties. Issue 3 (April 2015) - Guo, Zengcai; Mu, Jingbo; Chen, Bin
Abstract: The three-dimensional flower-like TNFePc hierarchical microstructures were fabricated by a simple solvothermal method. The as-obtained products exhibited high adsorption capacity and excellent simultaneously visible-light-driven photocatalytic performance for Rhodamine B (RB) under visible-light. Repetitive tests showed that the flower-like TNFePc hierarchical microstructures could maintain high catalytic activity over several cycles, and it had a better regeneration capability under mild conditions. Finally, a possible mechanism for the formation of three-dimensional flower-like TNFePc was suggested based on the evolution of morphology as a function of solvothermal time, which involved the initial formation of microparticles followed by their recrystallize to microspheres and transformation into three-dimensional flower-like hierarchical microstructures by mass diffusion and Ostwald ripening.